Instability in strongly magnetized accretion discs: a global perspective. Issue 2 (27th September 2017) - Das, Upasana; Begelman, Mitchell C.; Lesur, Geoffroy
Abstract: We examine the properties of strongly magnetized accretion discs in a global framework, with particular focus on the evolution of magnetohydrodynamic instabilities such as the magnetorotational instability (MRI). Work by Pessah & Psaltis showed that MRI is stabilized beyond a critical toroidal field in compressible, differentially rotating flows and, also, reported the appearance of two new instabilities beyond this field. Their results stemmed from considering geometric curvature effects due to the suprathermal background toroidal field, which had been previously ignored in weak-field studies. However, their calculations were performed under the local approximation, which poses the danger of introducing spurious behaviour due to the introduction of global geometric terms in an otherwise local framework. In order to avoid this, we perform a global eigenvalue analysis of the linearized MHD equations in cylindrical geometry. We confirm that MRI indeed tends to be highly suppressed when the background toroidal field attains the Pessah–Psaltis limit. We also observe the appearance of two new instabilities that emerge in the presence of highly suprathermal toroidal fields. These results were additionally verified using numerical simulations in pluto . There are, however, certain differences between the the local and global results, especially in the vertical wavenumber occupancies of the various instabilities, which we discuss in detail. We also study the global eigenfunctions of the most unstable modes in the suprathermal regime, which are inaccessible in the local analysis. Overall, our findings emphasize the necessity of a global treatment for accurately modelling strongly magnetized accretion discs.